P-177 Altered SHIP1-Protein Degradation in a Subset of IBD Patients. (March 2016) - Fernandes, Sandra; Ryan, James; Middleton, Frank; Chisholm, John; Kerr, William
Abstract : Background: SH2-containing Inositol Phophatase1 (SHIP1) is a key component of the PI3K pathway. It is expressed predominantly albeit not exclusively in hematopoietic cells. Germline SHIP1-deficiency in mice causes fatal eosinophilic pneumonia and severe ileitis in a phenotype mimicking human Crohn's Disease (CD). We therefore initiated a study to determine whether SHIP1 might be a contributing factor to CD or Ulcerative Colitis (UC) in humans. Methods: Blood samples are collected at the UCSF/San Francisco VA Hospital following recruitment from a 300 patient cohort. In the Kerr lab, Western blotting was used to determine the relative abundance of SHIP1 protein compared to a standardized control sample prepared from healthy donors. Samples displaying less than 10% of the SHIP1 protein found in the control were considered SHIP1-deficient. This finding was then confirmed on single-cell levels using icFlow for SHIP1. In parallel to these analyses, nucleic acids were extracted for DNA and RNA sequencing. Results: Of the 100 patients screened thus far in the cohort, SHIP1-deficiency was found in over 15% of both CD and UC patients. SHIP1-deficiency was stable as secondary blood draws taken from SHIP1-deficient patients still displayed the same phenotype several months later. SHIP1 exome sequencing did not reveal any inherent genetic defect in the INPP5D gene, and reduced SHIP1 protein levels did not result from low SHIP1 mRNA levels in these patients. Taken together these findings suggest a post-transcriptional mechanism for SHIP1-deficiency. Interestingly, treatment with proteasome inhibitor Mg132 allowed recovery of SHIP1 protein following 1h ex vivo culture in SHIP1-deficient but not SHIP1-sufficient patients, strongly suggesting involvement of the Ubiquitin-Proteasome System (UPS) in altered regulation of SHIP1 protein in SHIP1-deficient patients. Moreover, we observed that broad deubiquitinase (DUB) inhibition caused a reduction in SHIP1 protein levels in SHIP1-sufficient patients, but not in SHIP1-deficient patients, suggesting that a DUB that normally removes ubiquitin from SHIP1 is inactive or that its action is reduced in SHIP1-deficient patients. We are currently performing RNA-Seq on SHIP1-deficient patients to identify targets in the UPS system that may be dysregulated in this subset of IBD patients. Finally, we have recently identified a human cell line that closely mimics the phenotypes observed in the SHIP1-deficient patient samples. This will facilitate more detailed mechanistic studies as this project moves forward and more patients are recruited into our study. Conclusions: Results obtained thus far in our study indicate that altered SHIP1 protein stability, most likely due to a defective deubiquitinase, leads to increased protein degradation in SHIP1-deficient IBD patients. Since SHIP1-deficiency corresponds to a severe reduction, but not an absence of SHIP1 protein, this opens the possibility for targeting the residual protein with small molecule SHIP1 agonists.